Aquecimento vocal para o canto erudito: teoria e prática - Araujo, André Luiz Lopes de (2012)
INTRODUCTION: Before any performance, singing class, or even speech therapy intervention, a series of physical and vocal workouts is done. This practice is called vocal warm-up. OBJECTIVE: The objective of this work is to analyze vocal warm-up theory and practice in classical singing, from the perspective of different voice professionals: singing teachers, singers and speech therapists. METHOD: The study comprised 165 subjects from the three professional categories aforementioned: 86 singing teachers, 15 speech therapists, and 64 singers of both genders, aged between 22 and 70 years, in Brazil and Portugal. The subjects responded to an electronic closed-ended questionnaire characterizing the sample with information on gender, age, education, length of time in the profession and addressing questions related to the substance of this work. This is a quantitative cross-sectional descriptive study. The collected data was fed in EPIDATA 3.2 and, afterwards, statistical analysis was carried out using STATA 10.0. RESULTS: The tables were compiled based on thematic axes and distributed according to the professional groups surveyed: 65.1% of singing teachers, 75% of singers, and 86.6% of speech therapists utilize physiological warm-up, however, the great majority of singing teachers (98%), singers (95.3%), and speech therapists (93.3%) use vocalises as the main vocal warm-up method. CONCLUSION: Both principles and practice of vocal warm-up are placed within the context of oral tradition. The warm-up method mostly adopted by the great majority of the subjects of this study is vocalise